2008
DOI: 10.3390/molecules13102608
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman Spectral Measurements of 5-Fluorouracil in Saliva

Abstract: The ability of surface-enhanced Raman spectroscopy (SERS) to measure 5-fluorouracil (5-FU) in saliva is presented. The approach is based on the capacity of Raman spectroscopy to provide a unique spectral signature for virtually every chemical, and the ability of SERS to provide μg/mL sensitivity. A simple sampling method, that employed 1-mm glass capillaries filled with silver-doped sol-gels, was developed to isolate 5-FU from potential interfering chemical components of saliva and simultaneously provide SERS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 48 publications
(63 reference statements)
2
47
0
1
Order By: Relevance
“…This approach is based on the extreme sensitivity of SERS demonstrated by the detection of single molecules [19,20], the ability to measure very small samples (0.1 mL), and the ability to identify molecular structures of drugs through the rich vibrational information provided by Raman spectroscopy [21]. …”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on the extreme sensitivity of SERS demonstrated by the detection of single molecules [19,20], the ability to measure very small samples (0.1 mL), and the ability to identify molecular structures of drugs through the rich vibrational information provided by Raman spectroscopy [21]. …”
Section: Introductionmentioning
confidence: 99%
“…It utilizes vibrational signatures of bonds in a molecule for their highly sensitive, label-free, nondestructive and noninvasive detection. 24,25 SERS is being used increasingly in biomedical systems for biosensing and detection of target molecules such as recreational drugs, 26 therapeutic substances 27 and metabolites like cancer markers. 28 AuNPs have also been employed as intracellular probes facilitating cancer detection in saliva, 29 blood cells, 30 and tissues.…”
mentioning
confidence: 99%
“…130 5-FU was detected in saliva within the physiological range, 1–30 μg/mL. The 5-FU spectrum is dominated by the pyrimidine ring, trigonal ring plus C-F stretching mode, a ring plus C-H waging mode, a ring plus N-H wagging mode, and the symmetric C=O stretch.…”
Section: Metabolitesmentioning
confidence: 99%
“…It is suggested that the analytes interact with the metal NPs through the N 3 giving the analyte an upright geometry relative to the NP. 130 …”
Section: Metabolitesmentioning
confidence: 99%